(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
In the paper we considered one model of dynamic system in the form linear differential inclusion with control parameter and under conditions incomplete information about initial state. The control problem for ensemble trajectories of system according to minimax principle is researched. This control problem is study with a methods nonsmooth and multi-value analysis’s. The necessary and sufficient conditions of optimality are obtained.